RETRACTED: The COVID-19 fear, anxiety, and resilience among emergency nurses - Karimi Khordeh, Negar; Dehvan, Fazel; Dalvand, Sahar; Repišti, Selman; Ghanei Gheshlagh, Reza (Frontiers in Psychology, 2022)
Background Besides physical complications, COVID-19 is associated with psychological issues such as fear and anxiety. High resilience in nurses enables them to adopt positive coping mechanisms and successfully operate in the stressful environment of COVID-19 wards. The present study aimed to evaluate the correlation between COVID-19 fear and anxiety with resilience in the emergency nurses of the hospital affiliated with Kurdistan University of Medical Sciences (west of Iran) in 2021. Materials and methods This cross-sectional study was conducted on 295 emergency nurses of selected hospitals in Kurdistan province, Iran, in 2021. Data were collected using a demographic questionnaire, Fear of COVID-19 Scale (FCV-19S), Corona Disease Anxiety Scale (CDAS), and Connor-Davidson Resilience Scale (CD-RISC). Data analysis was performed in R software version 3.6.3. Results The mean scores of resilience, COVID-19 fear, and COVID-19 anxiety were 55.07 ± 19.82 (ranging from 0 to 100), 20 ± 7.37 (ranging from 7 to 35) and 36.48 ± 13.21 (ranging from 18 to 54) respectively. There was a negative and significant correlation between resilience with COVID-19 fear (r = −0.449, p = 0.001), COVID-19 anxiety (r = 0.458, p = 0.001). A significant correlation was observed between COVID-19 fear and anxiety, which indicated that if the other demographic variables remained unchanged, a one-unit increase in COVID-19 fear and anxiety decreased the mean resilience score by −0.66 (P = 0.008) and −0.34 (P = 0.015), respectively. Conclusion COVID-19 fear and anxiety were significantly correlated. Therefore, providing training courses for promoting resilience could reduce the fear and anxiety of nurses during the COVID-19 pandemic.